2020
DOI: 10.1111/iji.12480
|View full text |Cite
|
Sign up to set email alerts
|

MICA‐129 Met/Val polymorphism could be a genetic biomarker for Familial Breast Cancer in the Tunisian population

Abstract: Identification of candidate genes associated with susceptibility of breast cancer can have a significant impact at a cancer management national healthcare systems level, making genetic testing more affordable and cost‐effective. We have previously shown that the major histocompatibility complex class I‐related chain A (MICA) was related to breast cancer and plays an important role in modulating immune response mechanisms through NKG2D receptor activation. Compared to our previous study, in this work, we recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…N. Ouni and A.B. Chaaben found that MICA showed an association between family history of cancer, especially in younger patients (<40 years), and a Val/Val genotype (OR=2.03, P=0.02) [31].…”
Section: Othersmentioning
confidence: 98%
See 1 more Smart Citation
“…N. Ouni and A.B. Chaaben found that MICA showed an association between family history of cancer, especially in younger patients (<40 years), and a Val/Val genotype (OR=2.03, P=0.02) [31].…”
Section: Othersmentioning
confidence: 98%
“…Correcting the DNA mismatch progress [19] Cell cycle regulation genes TP53 Forming a homotetramer binding to TP53 response elements in DNA [21] PTEN Inhibiting of the DNA proliferation at the G1-S transition [24] DNAH11 Activating of p38 mitogen-activated protein kinase (MAPK) pathway [28] CDKN2A/B Inhibiting of the DNA proliferation at the G1-S transition [30] MICA Modulation in immune response regulation for cell cycles [31] Cell-to-cell adhesion genes CDH1 Coding E-cadherin adhesion protein [32] Metabolism genes PON1 Coding a multifactorial antioxidant enzyme [35] ABC Encoding large membrane proteins relating the energy dependent transport of xenobiotics [38] 3 Breast cancer susceptibility genes [10] . Two cohort studies by Engel and Fischer [11] indicated that the cumulative risk of first-time breast cancer at age 60 was 61.8% for BRCA1 mutation carriers, 43.2% for BRCA2 mutation carriers and 15.7% for non-carriers.…”
Section: Mlh1 /Msh2mentioning
confidence: 99%
“…Ouni N 2020 105 TMB status and PD-L1 expression Cai P 2020 101 body fluids represent a convenient, noninvasive and cheaper method for cancer diagnosis. Body fluids including serum or plasma, urine, saliva or sputum can be used in order to perform the biomarker detection.…”
Section: Genotypedmentioning
confidence: 99%
“…Recently were reported mutations of immune players as biomarkers, analyzed for specific human populations, Ahmad et al 104 reported the TNF-a308 G/A change and its significant association with breast cancer patients from north India and over the major histocompatibility complex class I-related chain A (MICA). Ouni et al 105 reported the MICA-129 Met/Val change as an inherited genetic biomarker contributing to an increased breast cancer risk in Tunisian women. Tumors are a heterogenous mix of different cells, with a wide array of metabolic, phenotypic and stemness-like properties, the immune responses or immune evasion that tumor cells induce at the host reflects these spectra.…”
Section: Strategies For the Search Of New Biomarkersmentioning
confidence: 99%